2018
DOI: 10.5152/turkjsurg.2018.3972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of limberg flap and oval flap techniques in sacrococcygeal pilonidal sinus disease surgery

Abstract: The Limberg flap and oval flap procedures both involve minimum morbidity and short hospital stay because they were not superior to one another regarding treatment effectiveness, complications, and recurrence in the pilonidal sinus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In randomised trials, the Limberg flap was found to be superior to midline closure [46,47]. In other studies, it was found to be comparable to the Karydakis operation [48][49][50] and to asymmetrical elliptical excisions [51,52]. A systematic review of the Limberg flap supported its equivalence to the Karydakis operation and its superiority over midline closure [44].…”
Section: Limberg Flapmentioning
confidence: 89%
“…In randomised trials, the Limberg flap was found to be superior to midline closure [46,47]. In other studies, it was found to be comparable to the Karydakis operation [48][49][50] and to asymmetrical elliptical excisions [51,52]. A systematic review of the Limberg flap supported its equivalence to the Karydakis operation and its superiority over midline closure [44].…”
Section: Limberg Flapmentioning
confidence: 89%
“…Flaps procedures are time consuming and technically more demanding with a risk for flap necrosis and hypoesthesia, though they are related to a low recurrence rate. 9 On the other hand, Karydakis addresses a lot of such issues. It is simple and easy to perform because it is technically less demanding.…”
Section: Discussionmentioning
confidence: 99%